О работе Порфмийского отряда Боспорской археологической экспедиции Института истории материальной культуры РАН в 2008 г. - Вахтина, М.Ю.; Столяренко, П.Г. (Археологічні дослідження в Україні, 2009)
During the protective research in Porphmium in 2008 at the north-eastern part of the settlement an area of Hellenistic fortifications was studied, and at the necropolis to the west from the settlement a vault made of limestone blocks and containing the 2nd c. BC burial was discovered.